Insight into structural features of soluble portions from cellulose, cellobiose and monosaccharide methanolysis by GC/MS and ESI FTICRMS. (May 2020) - Li, Zhan-Ku; Yan, Hong-Lei; Yan, Jing-Chong; Lei, Zhi-Ping; Ren, Shi-Biao; Wang, Zhi-Cai; Kang, Shi-Gang; Tian, Yu-Jiao; Pan, Chun-Xiu; Shui, Heng-Fu
Abstract: Methanolysis of biomass has attracted increasing attention due to it has some advantages, such as low critical points and strong hydrogen donation ability. In this paper, methanolysis of cellulose, cellobiose (sucrose), and monosaccharide (glucose) were performed to obtain methanol-soluble portions (MSPs). The relatively volatile or less polar species in the MSPs were analyzed with a gas chromatograph/mass spectrometer (GC/MS), and the polar species were identified with a negative-ion electrospray ionization Fourier transform ion cyclotron resonance mass spectrometer (FTICRMS). According to analysis with GC/MS, the MSPs include ethers, esters, ketones, acids, sugars, phenols, and furans. The analysis with FTICRMS shows that the polar compounds in the MSPs are O 1 – O 15 class species with 1–14 double bond equivalent (DBE) and 5–35 carbon atom number (CAN). The most abundant class species in MSPs from cellulose, sucrose, and glucose methanolysis are O 5, O 7, and O 7, respectively. The species in MSPs from sucrose and glucose methanolysis center at higher DBE value and more CAN than those in MSP from cellulose methanolysis. Meanwhile, the oxygen atom number of O 4 – O 10 class species in the MSPs were negatively correlated with the average DBE value. The results indicate that condensation intensively proceeded with the specific regularity during sucrose and glucose methanolysis. Highlights: More than 1000 species derived from cellulose, cellobiose, and monosaccharide were detected. Significant differences exist in the methanol-soluble portions. Condensation strongly occurred during cellobiose and monosaccharide methanolysis. Methanolysis may be a potential way for converting cellulose into chemicals or fuels.